Students' Music Preferences and Their Impact on Local Wisdom in SMPN 01 Sukadana - Wijaya, Andy; Sagala, Mastri Dihita; Silaban, Christianly Yery (Universitas Tanjungpura, 2025)
This study examines the relationship betwwen student musical preferences and their literacy of local wisdom in SMPN 01 Sukadana, Kayong Utara, Indonesia. The background of the problem lies in the increasing influence of global digital culture, particulart through platforms such as YouTube, Tiktok, and Spotify which shapes youth identity and shifts their engagement away from local cultural expressions. Using a qualitative case study design, data were collected through informal interviews, classroom observations, and document analysis of arts education lesson plans. The study involved 66 students and art teachers selected through purposive sampling. The findings show that students’ musical preferences are dominated by global popular genres such as pop, K-Pop, and EDM, while none of the respondents expressed interest in traditional music. This preference pattern correlates with a significantly low level of local cultural literacy, with 87.88% of students unaware of Sukadana’s local traditions, including the traditional Senggayong music, despite its inclusion in the formal curriculum. The analysis indicates that digital exposure, shifting socio-cultural values, and weak intergenerational transmission contribute to this cultural displacement, where global media overshadow local cultural knowledge. The study concludes that students’ musical preferences reflect broader cultural orientations shaped by digital ecosystems, which in turn influence their limited recognition of local wisdom. While the findings provide important insights into cultural dynamics in regional contexts, further research with broader samples is needed to strengthen generalization and develop pedagogical strategies to reinforce local cultural appreciation among youth.